ALIH KODE DALAM VIDEO BLOG KANAL YOUTUBE “NIHONGO MANTAPPU” - Putri, Widyawati Hema Mona; Andriyani, Anak Agung Ayu Dian (Universitas Negeri Padang, 2024)
This study aims to determine code switching in the form of language switching and the factors behind the occurrence of code switching that occurs in the interaction of students from Indonesia with students from Japan. The results of the study show that in interactions with video blogs on the YouTube channel